Liber mundi ou le vertige des contrastes chez Maurice G. Dantec - Isabelle Périer (ReS Futurae)
Maurice G. Dantec’s Liber mundi takes place in the contemporary world. These two novels can be described as “presentists” insofar as their stories constantly deviate from the present to finally return to it. On the one hand, they are detective novels but they gradually become critical cyberpunk novels. On the other hand, they evoke the past and the future, but only to bind them to the present. And finally they adopt a transcendental and sacred point of view to give meaning to the present disaster.